High-Level Aminoglycoside Resistance in Human Clinical Klebsiella pneumoniae Complex Isolates and Characteristics of armA-Carrying IncHI5 Plasmids - Zhang, Xueya; Li, Qiaoling; Lin, Hailong; Zhou, Wangxiao; Qian, Changrui; Sun, Zhewei; Lin, Li; Liu, Hongmao; Lu, Junwan; Lin, Xi; Li, Kewei; Xu, Teng; et al. (Frontiers in Microbiology, 2021)
Aminoglycosides are important options for treating life-threatening infections. However, high levels of aminoglycoside resistance (HLAR) among Klebsiella pneumoniae isolates have been observed increasingly frequently. In this study, a total of 292 isolates of the Klebsiella pneumoniae complex from a teaching hospital in China were analyzed. Among these isolates, the percentage of HLAR strains was 13.7% (40/292), and 15 aminoglycoside resistance genes were identified among the HLAR strains, with rmtB being the most dominant resistance gene (70%, 28/40). We also described an armA-carrying Klebsiella variicola strain KP2757 that exhibited high-level resistance to all aminoglycosides tested. Whole-genome sequencing of KP2757 demonstrated that the strain contained one chromosome and three plasmids, with all the aminoglycoside resistance genes (including two copies of armA and six AME genes) being located on a conjugative plasmid, p2757-346, belonging to type IncHI5. Comparative genomic analysis of eight IncHI5 plasmids showed that six of them carried two copies of the intact armA gene in the complete or truncated Tn1548 transposon. To the best of our knowledge, for the first time, we observed that two copies of armA together with six AME genes coexisted on the same plasmid in a strain of Klebsiella variicola with HLAR. Comparative genomic analysis of eight armA-carrying IncHI5 plasmids isolated from humans and sediment was performed, suggesting the potential for dissemination of these plasmids among bacteria from different sources. These results demonstrated the necessity of monitoring the prevalence of IncHI5 plasmids to restrict their worldwide dissemination.